Relationship Between Motivation and Work Discipline with Employee Performance - Imam Abrori; Via Lailatur Rizki; Fauzan Muttaqien (University of Riau Kepulauan, 2022)
The research entitled The Relationship between Motivation and Work Discipline with Employee Performance aims to analyze the effect of motivation and work discipline on employee performance at the Tofu factory employees CV. Serampang Jaya, Pujer, Bondowoso, both partially and simultaneously. The number of samples in this study amounted to 35 respondents with a sampling technique, namely the saturated sample technique or census. The data collection method used is by using questionnaires, interviews, and literature studies. The data analysis used includes validity test, reliability test, multiple linear regression analysis, classic assumption test consisting of multicollinearity test, heteroscedasticity test, and normality test, followed by hypothesis testing, namely partial test and simultaneous test, and continued with the coefficient of determination test. (R2). The results of the partial hypothesis test state that there is a positive and significant influence between the motivational variables on employee performance. The results of the partial test also state that there is a positive and significant influence between work discipline variables on employee performance. Meanwhile, the results of the simultaneous hypothesis test state that there is a positive and significant effect between the two independent variables, namely the motivation and work discipline variables on employee performance.